Emerging technology trends in the C&I rooftop solar market in India: Case study on datacentre – Retrofit with BIPV by U-Solar. (15th May 2022) - Kumar Singh, Atul; Prasath Kumar, V.R.; Krishnaraj, L.
Highlights: Business models: new growth drivers for increasing renewable energy adoption by the C&I segment. Key new trends that are being explored in the Indian market. Adoption of large-format modules. Cost analysis of onsite/rooftop solar installation models in India. Risks and challenges: existing buildings, design standards and codes, lack of manufacturers. Abstract: Commercial and industrial (C&I) applications have been the most active in india's onsite solar market. These applications account for almost three-quarters of the rooftop solar market in India. As a result of the COVID pandemic that began in 2020, solar installation slowed. The C&I market segment, on the other hand, is likely to recover and see a rise in solar installations. The C&I market has been forced to optimize its costs in light of the pandemic. In addition to helping companies accomplish these goals, rooftop solar systems with battery storage can also contribute to their social responsibility efforts. Rooftop solar systems with battery storage are also expected to grow in popularity. Battery prices are expected to reach 100 per kWh in roughly two years (by 2023), propelling the rooftop solar and battery storage sectors forward. Rooftop solar and Battery Energy Storage System (BESS) are ideal alternatives for behind-the-meter (BTM) applications in India due to their 90 GW of capacity. An Indian case study breaks down the costs of PV installation. This study examines the emerging technology trends in India's Commercial & Industrial Rooftop Solar market, as well as general advice for consumers and investors contemplating solar PV installations.